DOA BERSAMA DALAM KELUARGA KATOLIK DI WILAYAH III PAROKI MATER DEI MADIUN PADA MASA PANDEMI COVID-19 - Wulandari, Maria Gorethi Vivi; Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2022)
The Catholic family is one of the faith communities that participates in the Trinity of Christ, namely as priests, prophets and kings. One way that families can do this is by praying together in the family, as an embodiment of priesthood duties. In this Covid-19 pandemic situation, Catholic families are faced with a challenge, namely to remain faithful in carrying out prayer together as a family. This study aims to discuss the dynamics of prayer in Catholic families during the Covid-19 pandemic. The results showed that the implementation of prayer together in the family was mostly carried out directly. There are various kinds of prayers that are prayed in collective prayer. Catholic families also feel the benefits and challenges of carrying out prayer together in the family.